Tinjauan Aspek Ergonomi Lingkungan dan Keamanan Kerja pada Ruang Rekam Medis RS Tiara Bekasi - Hari Dwi Cahya; Muhammad Fuad Iqbal; Bangga Agung Satrya; Noor Yulia (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The application of good environmental ergonomics and occupational safety can help reduce the number of workplace accidents, improve employee welfare, and increase efficiency and productivity in the workplace. Therefore, research on Environmental Ergonomics and Occupational Safety is needed. To understand the contribution to scientific knowledge in the field of environmental ergonomics in medical record rooms, this study uses a qualitative descriptive research type to systematically describe Environmental Ergonomics and Occupational Safety. Observations in the medical record room at Tiara Hospital in Bekasi related to lighting in the medical record unit room found that the lighting in the medical record unit room was sufficient to assist staff in performing their duties. However, the lighting in the medical record document storage room (filing) is still uneven, and the medical record room door that cannot be locked poses a high risk to document security. Although there is a staff member on duty 24 hours a day, unauthorized individuals can still enter when the staff is inattentive. This can lead to unauthorized access to sensitive medical record documents, the risk of document theft or damage, and potential breaches of patient privacy. Suggestions include improving the lighting in the patient registration area to meet the recommended minimum standards and enhancing the security system, including ensuring that the medical record room door can be properly locked and considering the use of additional security technologies such as CCTV and access control systems.